pengertian perubahan pengertian perubahan sumber daya manusia menurut 7 orang pakar: pengertian perubahan sumber daya manusia menurut 7 orang pakar - A.putri Andini; Ilham tahier; Nurlela Nurlela; Natasyah Natasyah; Mutai nurfadilah aris; Tia juliawati; Ririn anita; Harmi Harmi (Universitas Slamet Riyadi, 2024)
The aim of this research is to determine changes in human resources. The method used in this research is qualitative methods and literature review), desk study by collecting and analyzing secondary data from various sources. The research results show that technology has a positive impact on human resource development, such as increasing efficiency, effectiveness, productivity, efficiency, motivation, satisfaction, loyalty and commitment of human resources. In an effort to support better and better quality human resources, a company or organization needs to make changes to obtain quality human resources and be able to